The Intertextual Relationships of Philosophy and Poetry in the Oeuvre of Pavle Goranović - KALEZIĆ RADONJIĆ, Svetlana (Anafora, 2023)
This paper analyzes the philosophical aspects of the poetry of Pavle Goranović, one of the most famous contemporary Montenegrin poets. A special emphasis is placed on Goranović’s dialogue with the ideas of Otto Weininger, Martin Heidegger, Emil Cioran, and Søren Kierkegaard, as well as on his strategies in transposing these ideas to his work. Although he directly refers to the aforementioned philosophers in only a few of his poems (“O zaboravu,” “Veliko spremanje,” “Svako buđenje,” “Regina Olsen,” “Vrtloglavica Serena Kjerkegora”...), the intertextual relationships are not equally intensive – in some cases it seems that the poet is more interested in the biography which preceded the shaping of the ideas; in some, Goranović uses as a starting point some of these philosophers’ ideas that he shares with them; and in some, he gives his own perspectives on the themata that contradict the viewpoints of the philosophers he mentioned explicitly or implicitly. The paper argues that this method occurs not only as a manner of artistic expression, which activates additional layers of ideas, but also as a conscious poetic tactic in the form of philosophical “bait” which demands the reader’s frequent re-engangement with the text, which ultimately enhances the aesthetic experience. The end of the paper sums up the most valent aspects of Goranovic’s poetry from the aesthetic point of view.